Adiabatic treatment for vibrational predissociation of water dimers with channel interactions. (August 2015) - Mineo, H; Lin, S H; Fujimura, Y
Synopsis: The results of calculated vibrational predissociation (VPD) of water dimers are presented. The VPD processes considered here are the followings: initially closed channel of symmetric stretching mode is excited by one quantum, and dissociate to two open channels of the bending mode excitation by one quantum in the donor and acceptor units. The VPD rate constants are calculated in the quantum mechanical approach under the adiabatic approximation. The channel interactions were taken into account in and between the initial and final states. The results obtained by quantum-mechanical approach are compared with both experimental and semi-classical trajectory calculation results.